Innovation in the Distribution of Educational Services through Information Technology to Improve Access to Islamic Education in State Madrasahs - Muamala, Siti; Fitri, Nurdina; Zohriah, Anis; Muin, Abdul (IJOSMAS, 2025)
Digital transformation in Islamic education systems, particularly in state madrasahs, requires innovation in the distribution of educational services to improve accessibility and quality of learning. This study analyses the implementation of information technology as a means of distributing Islamic educational services in state madrasahs in the digital era. The research method uses a qualitative approach through literature study and secondary data analysis from various state madrasahs that have implemented digital systems. The results show that the implementation of Learning Management Systems (LMS), digital madrasah applications, and hybrid learning platforms can increase access to education by up to 73% and learning effectiveness by 68%. The main challenges faced include the digital divide (42% of madrasahs), teacher digital literacy (35%), and infrastructure limitations (38%). This study recommends a technology-based educational service distribution model that is integrated with Islamic values, including human resource capacity building, equitable digital infrastructure, and strengthening a sustainable digital education management system